English language teaching in Costa Rica: reflections on emergent challenges - Mojica Barquero, Andrea (2021)
Teachers everywhere are always faced with new challenges as they engage in their pedagogical praxis; it is not easy to cater for students' needs (whether special or not) and bring about new ideas to teach and arouse students' interest and desire to learn, especially when one's job does not end at the workplace and continues at home. These are but a few of the hurdles teachers around the globe have to surmount. Indeed, teaching is a profession that is all too often misunderstood, underestimated, and harshly criticized. Teaching English as a Foreign Language (TEFL) in a country such as Costa Rica is no different. Indeed, foreign language teaching poses additional difficulties when considering that pedagogy is an act of communication, and in the teaching of English, language is both the means and the end of instruction. In this regard, the English language curriculum in Costa Rica is far from perfect, so it is not uncommon for English teachers here to have to start from scratch each time that they teach a new language course. Moreover, most English teachers in Costa Rica are native speakers of Spanish, which causes them to be discriminated against because they are considered inferior when compared with people coming from North America or Great Britain. This treatment is mostly unjustified as public universities in Costa Rica have sound English language programs with strong pedagogical components to train good teachers. Also, a little too often, native speakers who do not have any kind of pedagogical preparation are hired to be teachers by certain language academies, which can be rather counterproductive; the fact that, in theory, everyone knows their native language well is no guarantee that they can teach it successfully. A teacher is much more than a container of information. As a further matter, the year 2020 brought new challenges for (English) teachers all over the world; a pandemic was able to turn our lives upside down, which had to be adapted to fit into what was called "a new reality." Thus, teachers everywhere had to reinvent themselves, learn, relearn, and unlearn to teach in an education modality that they were not expecting. This condition exposed different limitations that had remained unnoticed up to this time in Costa Rica (and in other parts of the world). For example, students coming from low-income families had little or no access to the Internet, computers, and/or mobile devices; in this regard, remote learning made us even more unequal, and (English) teachers had to come up with alternative ways for students to continue their educational process. This required critical reflection and action as the reader will be able to see in the following pages. This book comprises a collection of essays written by students from the Master's Program in Education with an Emphasis on English Learning from Universidad Nacional, Costa Rica as part of their graduation project. In each of the manuscripts contained here, a Costa Rican English teacher reflects on and systematizes some of the challenges found in his or her professional practice along with possible solutions or recommendations. It is expected, therefore, that the information contained in this book may be of help to other English teachers around the world facing similar challenges.